Pengaruh Kepercayaan Diri dan Penguasaan Kosakata terhadap Keterampilan Berbicara Bahasa Inggris pada Mahasiswa Kelas D Pendidikan Bahasa Inggris Stambuk 2023 Universitas Negeri Medan - Yuliana Sari; Imei Wulandari; Efridayanti Gulo; Rama Yani Pakpahan; Rifdah Syabani Nasution (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The ability to speak English is an essential skill for students, yet many face challenges in this area, particularly due to low self-confidence and limited vocabulary. This research aims to analyze the influence of self-confidence and vocabulary mastery on the speaking skills of Class D students in the English Language Education program, Stambuk 2023, Medan State University. The research method employed is qualitative descriptive with data collection techniques through a questionnaire completed by 15 respondents. The research results indicate that students with high self-confidence and good vocabulary mastery are more fluent in speaking, while students who lack confidence or have limited vocabulary tend to experience difficulties in expressing ideas. These findings emphasize that enhancing self-confidence and enriching vocabulary can improve students' speaking skills. Therefore, a communication-based learning approach and more interactive speaking practice are recommended to enhance students' speaking abilities.